Abnormalities of lung mechanics in young asthmatic children. Issue 7 (July 1987) - Greenough, A; Loftus, B G; Pool, J; Price, J F
Abstract : Measurements of total compliance of the respiratory system by the weighted spirometer technique and of the functional residual capacity by helium gas dilution were attempted in 86 asthmatic children aged 2.2-7.9 years. In all but six of the 86 children reliable measurements could be obtained. Significantly raised functional residual capacity was detected in children with asthma of all degrees of severity. The compliance of the respiratory system was significantly abnormal (reduced) only in children who had symptoms at the time of measurement or who had chronic persistent asthma. The results indicate that these measurements are well tolerated in young asthmatic children. Further work needs to be undertaken to assess the value of this technique in following the response to treatment.